Growth Assessment of Young Plantation of Santalum album with Dalbergia latifolia as Host - Arunkumar, A.N.; Joshi, Geeta; Warrier, Rekha R (Indian Forester, 2022)
Indian Sandalwood (Santalum album) is a highly valued partial root parasite tree and the prized heartwood is considered as 'wood of choice' in carving and oil obtained from steam distillation of heartwood is regarded as 'aroma of choice' in perfume industry. Due to large scale reduction in natural population, it is categorised as 'threatened' by International Union for Conservation of Nature. Earlier it was recognised as Royal tree in Karnataka and Tamil Nadu, because of which even basic information about growth was lacking. With the relaxed government policies and the increased demand for heartwood and oil, farmers and entrepreneurs are motivated to cultivate Sandalwood. Presently, numerous plantations are being raised and documenting growth data from these plantations is very important. During a survey of Sandalwood plantations in Karnataka, an eight year old unique Sandalwood plantation was identified which had Indian Rosewood (Dalbergia latifolia) as host and growth data was collected. The Sandalwood trees girth at breast height (GBH) varied from 13.9 to 31.2 cm with an average GBH of 19.24 cm and average tree height was 6.02 m varying from 5.0 to 9.5 m. Rosewood had mean tree height and GBH of 8.72 m and 29.18 cm, respectively. Core samples collected from Sandalwood trees above 30 cm girth did not show any indications of heartwood formation. This study would augment necessary information required for developing package and practices on Sandalwood cultivation.